Dopamine sensing and measurement using threshold and spectral measurements in random lasers - Ismail W.Z.W.; Liu G.; Zhang K.; Goldys E.M.; Dawes J.M. (OSA - The Optical Society, 2024)
We developed a novel dopamine sensing and measurement technique based on aggregation of gold nanoparticles in random lasers. Dopamine combined with copper ions triggers the aggregation of gold nanoparticles and thus affects the performance of random lasers. Dopamine sensing can be achieved using four parameters which are sensitive to the presence of dopamine, that is emission peak shift, emission linewidth, signal-to-noise ratio (peak emission intensity / noise) and random lasing threshold. The dopamine is most sensitively detected by a change in the emission linewidth with a limit of detection of 1 10-7 M, as well as by an increase in the lasing threshold. The dopamine concentration from 1 10-7 M to 1 10-2M can be determined by calibrating with the laser threshold. 2015 Optical Society of America.